Efeitos antinociceptivo e anti-inflamatório da eletroacupuntura na artrite induzida por zymosan na articulação temporomandibular de ratos : participação do sistema endocanabinóide - Gondim, Delane Viana (2012)
Electroacupuncture (EA) and cannabinoids have been reported to have anti-inflammatory and antinociceptive effects in experimental models of inflammatory pain. The present study investigated these effects on zymosan-induced acute arthritis of the rat temporomandibular joint (TMJ). Male Wistar rats were injected with saline or zymosan (control group; 2 mg) into the TMJ. Low frequency EACP (10 Hz, 30 min) was performed at acupoints (LI4, LI11, ST36, ST44) or sham points 2 h after or 1 h before zymosan administration. CB1 and CB2 cannabinoid receptor antagonists, respectively, AM251 and AM630 (3mg/kg, i.p.) were administered before EA treatment. Mechanical hypernociception was accessed by the electronic Von Frey method after zymosan administration. Rats were sacrificed 6 h after zymosan administration and the joint was removed for histopathological analysis, myeloperoxidase activity assessment, vascular permeability observations and immunohistochemical analysis to TNFα, COX-2 and iNOS. Gene expression of CB1 and CB2 receptors of nervous tissue in the region of the spinal trigeminal tract was performed after sacrifice of the TMJ arthritic animals in the times of 6th and 24th hour after zymosan injection. The results showed that EA inhibited zymosan -induced hypernociception compared with the control group and with the sham group (p< 0.05). AM251 significantly reversed the antinociceptive effect of EACP, suggesting that the CB1 receptor is involved in this effect. The results showed that EACP inhibited inflammatory parameters such as neutrophil migration, vascular permeability and TNF-α, COX-2 and NOSi expression in the TMJ compared with the sham group (p< 0.05). The inflammatory parameters assessment with the cannabinoids antagonists, we found that AM630 reverses the anti-inflammatory effect of EACP. The CB1 and CB2 gene expression in 6th hour after zymosan-induced arthritis, showed up-regulation in the animal group treated with EACP. In the 24th hour, it was observed down- regulation of CB2 gene expression at EACP group when compared to 6th hour, while for the CB1 receptor, it was observed a higher gene expression in relation to 6th hour. EACP in the acupoints, LI4, LI11, ST36 and ST44 produced antinociceptive and anti-inflammatory effects in the arthritis induced by zymosan in the TMJ rats. These effects appear to be mediated through CB1 and CB2 cannabinoid receptors activation. Based in our results, we suggest that EACP can be used in TMJ inflammatory arthropathy treatment.